Prevalence of Vitamin D Deficency and Its Related Risk Factors Among Students in Fangshan District, Beijing, China. (14th June 2022) - Zhao, Xia; Zhao, Yao; Zhang, Dongran; Huang, Shaoping; Zhang, Mengmeng
Abstract: Objectives: To study the prevalence of Vitamin D deficency among students and explore factors related to Vitamin D deficency. Methods: This is a cross-sectional prevalence study in 529 students aged 6 to 13 years old. The study was conducted from October to November 2019 in Fangshan District, Beijing, China. 25-Hydroxyvitamin D was measured by a chemiluminescent assay.Vitamin D deficency cut off was set at serum 25(OH)D concentration of <12 ng/mL. Results: The overall serum 25(OH)D concentration was 19.76 ± 6.06 ng/mL. The mean serum 25(OH)D concentrations in boys and girls were 20.91 ± 5.66 ng/mL and 18.52 ± 6.25 ng/mL, respectively. The overall prevalence of Vitamin D deficency was 20.79%. The rates of Vitamin D deficency in boys and girls were 12.00% and 30.31%, respectively. Logistic regression showed that Vitamin D deficency was worse in girls, students who were in higher grades and didn't have vitamin supplements. Conclusions: The rate of Vitamin D deficency among students was high, interventions for high-risk students should be taken. Funding Sources: Beijing Center for Diseases Control and Prevention.